A precarious success : land reform and governance of the commons at the Amangcolosi Community Trust - Tekié, Amy (My University, 2016)
This study explores the land restitution experience of the Amangcolosi Community Trust, to understand what factors have allowed them to build a thriving land reform project in a terrain riddled with dysfunctional community property institutions and under-utilised land. The case of the neighbouring Gayede Trust, with a shared history, is used as a secondary case for comparison. The research considers what factors contribute to effective communal property management, as well as the role of government, the traditional authority, and commercial partners in contributing to or hindering success. It also explores what factors have allowed for alleged co-option of resources by elites, and the role of corruption and mismanagement by government in jeopardising the community’s success. Finally, it discusses the importance of accountability from both the top-down and bottom-up if land reform is to avoid ongoing repetitions of the tragedy of the commons.
MA, Development Studies Research report University of the Witwatersrand Final submission 2 November 2016
Keywords: Land reform--South Africa; Land tenure--South Africa; Restitution--Economic aspects--South Africa; Rural development--South Africa